Pemberdayaan Masyarakat Desa Balongjeruk Melalui Pelatihan Perawatan Jenazah: Studi Kasus Di Kecamatan Kunjang, Kabupaten Kediri - ali, sapri; Farihatuzzulfa Inda Maula; Luluk Nur Hidayati; Silvy Mambaul Avivah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
This community empowerment research aims to enhance the capabilities of residents in Balongjeruk Village, Kunjang District, Kediri Regency, through training in Islamic funeral rites and corpse care. The training addresses the lack of knowledge and skills among the community members in properly handling the deceased according to Islamic law, which often poses social and religious challenges in the village. The research employed a Participatory Action Research (PAR) approach, actively involving community members in observation, discussions, training, and evaluation processes. The results indicate a significant improvement in the community’s understanding and ability to perform all funeral rites, including washing, shrouding, funeral prayer, and burial. The training also reduced fear and negative stigma regarding corpse care and strengthened social and religious values within the community. Residents became more independent and capable of fulfilling the Islamic communal obligation (fardhu kifayah) in managing the deceased without relying entirely on religious leaders. This program is expected to serve as a model for community empowerment in similar regions. Recommendations for follow-up actions include continuous training, the formation of village funeral care groups, and collaboration with religious institutions to enhance capacity.